The prevalence of pathogens in ticks collected from humans in Belgium, 2021, versus 2017 - Philippe, Camille; Geebelen, Laurence; Hermy, Marie R. G.; Dufrasne, François E.; Tersago, Katrien; Pellegrino, Alessandro; Fonville, Manoj; Sprong, Hein; Mori, Marcella; Lernout, Tinne (Parasites & vectors, 2024)
Ticks carry a variety of microorganisms, some of which are pathogenic to humans. The human risk of tick-borne diseases depends on, among others, the prevalence of pathogens in ticks biting humans. To follow-up on this prevalence over time, a Belgian study from 2017 was repeated in 2021. During the tick season 2021, citizens were invited to have ticks removed from their skin, send them and fill in a short questionnaire on an existing citizen science platform for the notification of tick bites (TekenNet). Ticks were morphologically identified to species and life stage level and screened using multiplex qPCR targeting, among others, Borrelia burgdorferi (sensu lato), Anaplasma phagocytophilum, Borrelia miyamotoi, Neoehrlichia mikurensis, Babesia spp., Rickettsia helvetica and tick-borne encephalitis virus (TBEV). The same methodology as in 2017 was used. In 2021, the same tick species as in 2017 were identified in similar proportions; of 1094 ticks, 98.7% were Ixodes ricinus, 0.8% Ixodes hexagonus and 0.5% Dermacentor reticulatus. A total of 928 nymphs and adults could be screened for the presence of pathogens. Borrelia burgdorferi (s.l.) was detected in 9.9% (95% CI 8.2-12.0%), which is significantly lower than the prevalence of 13.9% (95% CI 12.2-15.7%) in 2017 (P = 0.004). The prevalences of A. phagocytophilum (4.7%; 95% CI 3.5-6.3%) and R. helvetica (13.3%; 95% CI 11.2-15.6%) in 2021 were significantly higher compared to 2017 (1.8%; 95% CI 1.3-2.7% and 6.8%; 95% CI 5.6-8.2% respectively) (P < 0.001 for both). For the other pathogens tested, no statistical differences compared to 2017 were found, with prevalences ranging between 1.5 and 2.9% in 2021. Rickettsia raoultii was again found in D. reticulatus ticks (n = 3/5 in 2021). Similar to 2017, no TBEV was detected in the ticks. Co-infections were found in 5.1% of ticks. When combining co-infection occurrence in 2017 and 2021, a positive correlation was observed between B. burgdorferi (s.l.) and N. mikurensis and B. burgdorferi (s.l.) and B. miyamotoi (P < 0.001 for both). Although the 2021 prevalences fell within expectations, differences were found compared to 2017. Further research to understand the explanations behind these differences is needed.